2018
DOI: 10.1080/1828051x.2018.1551071
|View full text |Cite
|
Sign up to set email alerts
|

Stimulatory effects of fish oil and vitamin E on ovarian function of laying hen

Abstract: In recent years, there has been an increase in the consumption of omega-6 fatty acids (FAs) over omega-3. Moreover, the antioxidant nature of oil supplemented diet in human and animal studies is not clear. In this work, the n-3 effects on hen ovarian cells, ovarian dynamics, serum FA profiles and expression level of apoptosis genes in the presence or absence of vitamin E were studied. Sixty-eight laying hens were randomly divided into four groups and the groups were fed the following diets: basal diet þ1.5% su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…To minimise the loss of membrane PUFAs during freeze–thaw procedure, dietary supplementation of PUFAs or direct addition of PUFAs enriched sources in cryopreservation medium has been reported in human and animals trials (Abavisani, Arshami, Naserian, Kandelousi, & Azizzadeh, ; Abdi‐Benemar et al, ; Esmaeili, Shahverdi, Alizadeh, Alipour, & Chehrazi, ; Habibi et al, ; Kaeoket, Sang‐urai, Thamniyom, Chanapiwat, & Techakumphu, ; Safarinejad, ; Towhidi, Zeinoaldini, Ardebili, Dadashpour Davachi, & Nasiri, ). Dietary supplementation with fish oil increased the level of the n–3 fatty acids in the serum (Nateghi, Alizadeh, Jafari Ahangari, Fathi, & Akhlaghi, ; Safarinejad, ) and sperm plasma membrane (Alizadeh, Esmaeili, Shahverdi, & Rashidi, ; Esmaeili et al, ; Safarinejad, ). Moreover, improvement in frozen‐thawed sperm quality by dietary supplementation with PUFAs has been well established in previous studies (Esmaeili et al, ; Habibi et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…To minimise the loss of membrane PUFAs during freeze–thaw procedure, dietary supplementation of PUFAs or direct addition of PUFAs enriched sources in cryopreservation medium has been reported in human and animals trials (Abavisani, Arshami, Naserian, Kandelousi, & Azizzadeh, ; Abdi‐Benemar et al, ; Esmaeili, Shahverdi, Alizadeh, Alipour, & Chehrazi, ; Habibi et al, ; Kaeoket, Sang‐urai, Thamniyom, Chanapiwat, & Techakumphu, ; Safarinejad, ; Towhidi, Zeinoaldini, Ardebili, Dadashpour Davachi, & Nasiri, ). Dietary supplementation with fish oil increased the level of the n–3 fatty acids in the serum (Nateghi, Alizadeh, Jafari Ahangari, Fathi, & Akhlaghi, ; Safarinejad, ) and sperm plasma membrane (Alizadeh, Esmaeili, Shahverdi, & Rashidi, ; Esmaeili et al, ; Safarinejad, ). Moreover, improvement in frozen‐thawed sperm quality by dietary supplementation with PUFAs has been well established in previous studies (Esmaeili et al, ; Habibi et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The decreased ROS levels in female follicular fluid increased the number of follicles and increased fertility (Attaran et al, 2000;Elizur et al, 2014). The presence of vitamin E along with omega 3 in the diet can play a role in boosting follicle growth (Nateghi et al, 2019). In the present study, it was shown that the use of vitamin E and L-carnitine increased the expression of TGF-β in the ovary, which led to the improved follicle function and pregnancy; this could be due to the improved inflammation in the tissue as well as the better function of the ovary.…”
Section: Rosmentioning
confidence: 99%